2006
DOI: 10.1161/circulationaha.105.561647
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in the Management and Clinical Outcome of Stable Angina

Abstract: on behalf of the Euro Heart Survey Investigators Background-We sought to examine the impact of gender on the investigation and subsequent management of stable angina and to assess gender differences in clinical outcome at 1 year. Methods and Results-The Euro Heart Survey of Stable Angina enrolled patients with a clinical diagnosis of stable angina on initial assessment by a cardiologist. Baseline clinical details and cardiac investigations planned or performed within a 4-week period of the assessment were reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
244
1
20

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 400 publications
(283 citation statements)
references
References 49 publications
18
244
1
20
Order By: Relevance
“…Physicians in their turn also tend to be slower in relating chest pain in women to coronary diseases, even more so if women present symptoms in emotional rather than matter-of-fact ways [14]. Women are also given exercise ECG and coronary angiography tests less frequently and receive therapy in line with prevailing guidelines less often [15]. Apparently, physicians work on the basis that angina pectoris in women is of an innocent nature.…”
Section: Angina Pectorismentioning
confidence: 99%
“…Physicians in their turn also tend to be slower in relating chest pain in women to coronary diseases, even more so if women present symptoms in emotional rather than matter-of-fact ways [14]. Women are also given exercise ECG and coronary angiography tests less frequently and receive therapy in line with prevailing guidelines less often [15]. Apparently, physicians work on the basis that angina pectoris in women is of an innocent nature.…”
Section: Angina Pectorismentioning
confidence: 99%
“…There is also evidence that women, for no apparent medical reason, are not offered the same treatment as men, a phenomenon that raises the question of gender bias. Many studies, for example, show that women are less likely than men to receive more advanced diagnostic and therapeutic interventions [6][7][8][9][10][11].…”
mentioning
confidence: 99%
“…A study of 3779 patients with stable angina showed that in women with proven coronary disease, revascularization procedures were used less frequently than in men 7. Meanwhile, at 1 year of follow‐up, the combination of antiplatelet and lipid‐lowering therapies was prescribed less for women than for men.…”
Section: Discussionmentioning
confidence: 99%
“…Female patients have more complex signs and symptoms of ischemia, and the variation in reproductive hormone levels may play a role in CHD pathophysiology and response to treatment. In both acute and chronic settings, several studies have shown that women, compared with men, are less aggressively treated with evidence‐based therapies and less often undergo invasive procedures 4, 5, 6, 7, 8. However, less is known about the relationship of psychosocial factors, sex, and clinical outcomes among patients with CHD 9, 10, 11, 12, 13.…”
Section: Introductionmentioning
confidence: 99%